2013
DOI: 10.1177/1071100713517101
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Treatment of Advanced Ankle Arthropathy by Total Ankle Replacement or Ankle Fusion

Abstract: Level II, prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 31 publications
3
78
0
1
Order By: Relevance
“…This needs to be factored in the interpretation of studies that examine TAA outcomes over time or compare study results to more historical older cohorts. Our finding of increasing age of patients undergoing TAA in the U.S. confirms a similar finding from a recently published study that used NIS data from 2000–10 (14). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This needs to be factored in the interpretation of studies that examine TAA outcomes over time or compare study results to more historical older cohorts. Our finding of increasing age of patients undergoing TAA in the U.S. confirms a similar finding from a recently published study that used NIS data from 2000–10 (14). …”
Section: Discussionsupporting
confidence: 91%
“…A previous study of 10-years of NIS data found findings similar to our study with an increasing volume of TAA from 2000–10 and increasing patient age (14). Our study has several important observations that merit further discussion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All these changes have in 1 form or another been implemented in the initially released and current Salto TalarisÔ total ankle prosthesis. The potential for a learning curve effect could also exist because the implantation of total ankle replacement systems in the United States has evolved from limited use in the late 1990s to commonplace at present (86,87). For instance, the Salto Ò mobile version prosthesis data included this learning curve (20,24,(31)(32)(33)(34)36); however, the Salto TalarisÔ Total Ankle Prostheses data included data from surgeons experienced with the implantation of total ankle replacement systems in general (24,(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…This cadaveric study uniquely examines the impact of neutral, and simulated uneven surfaces on the ankle joint after hindfoot stabilization and demonstrates decrease force and contact area, while ultimately determining that contact stress was unchanged. Although there is limited information on this question from a biomechanical standpoint, there are a number of long-term retrospective clinical series that have demonstrated radiographic changes in the ankle joint after triple arthrodesis [2,5]. Interestingly, these clinical studies reported 30% to 40% of radiographic changes of the ankle approximately 25 years after a triple arthrodesis.…”
mentioning
confidence: 99%